Utilization of biomass and waste resources for renewable hydrogen production: A comprehensive study - Karayel, G. Kubilay; Javani, Nader; Dincer, Ibrahim (TAYLOR & FRANCIS INC, 2023)
The current study investigates the biomass and waste-based potential for green hydrogen production in Turkey. The biomass sources are identified based on the collection of municipal, industrial, animal, agricultural, and forestry wastes. The potential of each city is estimated and discussed for a feasible hydrogen economy. Using the legitimate government data obtained from the governmental sources, the capacities of the available biomass potential for different cities in tons of oil equivalent are considered annually for the analysis and assessment. The power production is considered through using gasification and incineration systems, where the final product is hydrogen. The main idea is to prepare hydrogen maps in detail for each region in Turkey, based on the biomass energy potential through employing the gasification and incineration approaches. The results show that Turkey's total green hydrogen production potential using available biomass resources is about 1.66 megatons/year. Konya, Adana, Ankara, Sanliurfa, and Manisa are listed as cities with the highest green hydrogen production potential with an annual production of 129.53, 78.82, 64.42, 64.2, and 53.63 kilotons, respectively. The results of the study are expected to help policymakers to use renewable energies for planning and strategizing new local and global acts for the country and help to tackle fossil-fuel-based issues. This, in turn, can be considered in the context of the current policies of the local communities to supply the required energy.
Keywords: Green hydrogen; biomass; wastes; gasification; incineration; syngas; >; SOLID-WASTE; ENERGY; POWER; ECONOMY; ETHANOL; SYSTEM; GAS; Energy & Fuels; Engineering; Environmental Sciences & Ecology